A sociolinguistic Study of the Effects of Yoruba-English Code-mixing on the Yoruba Language - Oluwaseun Iyanuoluwa Owolola (JURNAL ARBITRER, 2018)
This work investigates the effects of Yoruba-English Code-mixing on the Yoruba language. From a sociolinguistic perspective, it examines the reasons why people code-mix English with Yoruba and the effects of the code-mixing on the Yoruba language. The study is modeled after Crystal's (2000) theory of language death. Data for the study was collected with the use of self-designed questionnaire which was administered to 100 respondents. The analysis of the responses shows that a number of lexical items of the Yoruba language have been lost by the native speakers as a result Yoruba-English code-mixing. It also reveals that this sociolinguistic phenomenon may hamper the growth and development of the Yoruba language as it has become more convenient for Yoruba speakers to code-mix than to coin new words for new concepts, items or ideas. The study, therefore, concludes that uncontrolled Yoruba-English code-mixing may render the use of the Yoruba language moribund, consequently leading to the death of the language. It is recommended that the native speakers of Yoruba should make conscious efforts to use "pure" Yoruba, minimizing the use of code-mix.Â  Â